Current treatment strategies for ruptured abdominal aortic aneurysm - Peters, Andreas; Hakimi, Maani; Erhart, Philipp; Wortmann, Markus; Bischoff, Moritz; Böckler, Dittmar (Langenbeck's archives of surgery, 2016)
BackgroundRuptured abdominal aortic aneurysm (rAAA) represents one of the most challenging emergencies in surgery. Open repair (OR) is associated with relevant morbidity and mortality and has not been reduced significantly over the last decade. The introduction of endovascular aneurysm repair (EVAR) and its meanwhile common use in the treatment of rAAA has raised the demand for randomised controlled trials (RCTs) in order to resolve a potential superiority of either OR or EVAR.PurposeThis review discusses the current treatment strategies in rAAA repair including diagnostics, peri-operative management and results of OR and EVAR, focussing on RCTs comparing both modalities.ResultsThirty-day mortality after OR and EVAR shows no significant difference in published RCTs. In particular with respect to OR, 30-day mortality was much lower than anticipated throughout all RCTs ranging from 18 to 37 %. EVAR for rAAA resulted in reduced in-hospital stay. Limitations of all except one RCT are low patient recruitment and exclusion of haemodynamically unstable patients.ConclusionsOR and EVAR need to be provided for rAAA. Despite lacking evidence, EVAR is the first choice treatment in experienced high-volume vascular centres. Low mortality rates in all RCTs raise the question if aortic surgery should be centralised.
Gesehen am 17.09.2019